Materiais adsorventes à base de quitosana/pectina para remoção de Pb (II) em meio aquoso - Matos, Henrique Kirylko de (2020)
The study on natural polysaccharides has gained prominence due to the beneficial effects on the environment and disease prevention to humans. For the present work, a biodegradable adsorbent was developed from natural polysaccharides to remove Pb (II) from wastewater. Chitosan (QT) and pectin (PEC) polysaccharides were used at a concentration of 1% (QT) and 2.5% (PEC). Chitosan (QT) is a natural and cationic biopolymer, obtained mainly through the partial deacetylation reaction of chitin, which is the second most abundant natural biopolymer on the planet, extracted mainly from the crustacean exoskeleton. Pectin (PEC) is an anionic polysaccharide, soluble in water and extracted mainly from plant cell walls, PEC extraction occurs through thermal and mechanical treatments. The new materials were characterized and applied to the adsorption process. From the infrared spectroscopy (FT-IR), characteristic peaks of pure polysaccharides and in the polymer blend were observed, proving the formation of the material. The TGA / DTG curves showed that the material has thermal stability close to 250 ºC. In addition, material stability was observed from the micrographs, where it indicated homogeneous surfaces with no fractures. The adsorption process between the adsorbent-adsorbate (QT / PEC and Pb (II)) was proven from the result of the EDS and DSC techniques. In these cases, the materials were evaluated before and after the adsorption process. The EDS spectra indicated the presence of the metal Pb (II) after adsorption. The DSC curves showed a shift in the endothermic peak at 7 ºC. The presence of carboxylic groups (indicated by FT-IR) ratified Boehm's titration values indicating the possible electrostatic attraction between these negatively charged groups at pH 4 (ensured by pH (pcz) assays). There was a strong interaction between adsorbent-adsorbate from the adjustments of theoretical adsorption models with values of maximum amount adsorbed in the balance of 112 mg g-1. In this way, we can conclude that the prepared material was characterized and applied to the Pb (II) metal adsorption process, presenting satisfactory results, even after the process was reused repeatedly three times.